Work-skill development for death row prisoners: A labour law and human rights perspective - Azzahra Rizki Ananda; Sugeng Dwiono (Journal of Law Science, 2026)
This study examines work-skill development for death row prisoners in Indonesian correctional institutions from the perspectives of correctional law, labour law, and human rights. The central gap addressed in this article is the absence of a specific legal framework that determines whether, how, and under what safeguards death row prisoners may participate in work-skill development programs. This study uses normative legal research with statutory, conceptual, and case approaches. The legal materials are analyzed through grammatical, systematic, and teleological interpretation, combined with doctrinal reasoning on the hierarchy of norms, restriction of rights, and state responsibility. The analysis shows that Indonesian correctional law recognizes prisoners’ rights to guidance, occupational safety, wages, or work-performance premiums, while human rights law requires humane treatment and protection of inherent dignity. However, the current framework does not specifically regulate death row prisoners, creating legal uncertainty, institutional discretion, unequal access, and risks of exploitation. The novelty of this article lies in the formulation of “custodial vocational protection” as a normative model that distinguishes rights-based work-skill development from ordinary employment and exploitative prison labour. This article argues that death row prisoners are not workers in a conventional employment relationship, but they remain legal subjects whose participation in correctional work programs must be voluntary, safe, non-discriminatory, psychologically assessed, fairly incentivized, and institutionally accountable.